1994
DOI: 10.1002/col.5080190404
|View full text |Cite
|
Sign up to set email alerts
|

Rod contribution to large‐field color matching

Abstract: The linear algebraic features of foveal colorimetry do not apply to 10° degree colorimetric fields. A light presented as a foveal 2° field stimulates the three classes of cone photoreceptors, and a light presented as a 10° field stimulates the cone and rod photoreceptors. While no more than three primary lights are required to match either of these lights, large‐field color matches with three primaries do not obey Grassmann's laws of linearity because the relative contribution of the rod signal to a color matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…When both rods and cones are operational, rods influence all aspects of color vision ( Lythgoe, 1931 ; Gilbert, 1950 ; Trezona, 1970 ; Stabell and Stabell, 1975a , b, 1976 , 1979 , 1994 ; Smith and Pokorny, 1977 ; Montag and Boynton, 1987 ; Buck, 1997 ; Cao et al, 2005 ). In trichromatic observers, large field and peripherally viewed lights stimulate four different photoreceptor classes at mesopic light levels and as light level decreases, large field color matches made with three primaries do not obey Grassman’s laws ( Shapiro et al, 1994 ). Conversely, the dichromatic retina behaves similarly to the trichromatic retina with large or peripherally viewed mesopic stimuli when rods operate as the third photoreceptor class ( Smith and Pokorny, 1977 ).…”
Section: Rod Contributions To Mesopic Color Visionmentioning
confidence: 99%
“…When both rods and cones are operational, rods influence all aspects of color vision ( Lythgoe, 1931 ; Gilbert, 1950 ; Trezona, 1970 ; Stabell and Stabell, 1975a , b, 1976 , 1979 , 1994 ; Smith and Pokorny, 1977 ; Montag and Boynton, 1987 ; Buck, 1997 ; Cao et al, 2005 ). In trichromatic observers, large field and peripherally viewed lights stimulate four different photoreceptor classes at mesopic light levels and as light level decreases, large field color matches made with three primaries do not obey Grassman’s laws ( Shapiro et al, 1994 ). Conversely, the dichromatic retina behaves similarly to the trichromatic retina with large or peripherally viewed mesopic stimuli when rods operate as the third photoreceptor class ( Smith and Pokorny, 1977 ).…”
Section: Rod Contributions To Mesopic Color Visionmentioning
confidence: 99%
“…Thornton (Thornton 1997) found that the inter-observer differences appeared to be large for anti-prime color (AP: 497-579-653 nm) monochromatic matching primaries, but small for prime color (PC: 452-533-607 nm) spectral composition. Since the average age of Thornton's six observers was 56 years and the average age of the CIE observer was 32 years, lens yellowing could be a factor explaining some of the discrepancies between the average data of the two groups (Shapiro et al 1994). In a re-analysis of Thornton's data, Abraham (Ábrahám et al 1995) did indeed find that there was a difference between the mean chromaticity of matches made by old and young observers when using the AP primaries, causing increased overall variability.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large body of psychophysical literature documenting the validity of this condition, some of which is listed here. [1][2][3][4][5][6][7][8][9] In addition, objective measures of visual response using infrared technology have demonstrated that primarily the scotopic spectrum, and thus rods, controls pupil size at typical interior light levels. 10,11 Lighting practice has largely ignored all this information and thus often appears bewildered when a pure cone response (the V(l) calibrating function based on observers viewing a 2°visual field) does not agree with many brightness experiences in real lit environments.…”
Section: S Berman Phd (Lawrence Berkeley Laboratories)mentioning
confidence: 99%